(untitled) (Chemical Engineering Research Bulletin, 2011)
In this paper, an investigation is made to study the boundary layer flow over a porous flat plate with diffusion of chemically reactive species undergoing first-order reaction and subject to suction and injection. In this analysis, the variable plate concentration is considered. Using similarity variable technique, the governing partial differential equations are transformed into a set of self-similar ordinary differential equations which are solved by shooting method. The study reveals that for the increase of suction at the plate both velocity and concentration boundary layer thicknesses decrease and for increasing injection both thicknesses increase. The concentration at a fixed point decreases with increasing values of the Schmidt number Sc, the reaction rate parameter beta and the power-law exponent n. For a fixed point, with increase of beta the magnitude of concentration gradient initially increases and then after a point it decreases. The rate of solute transfer from the plate increases with reaction rate parameter and power-law exponent. Key words: Boundary layer flow; diffusion; first-order chemical reaction; porous flat plate; suction/injection DOI: http://dx.doi.org/10.3329/cerb.v15i1.6464 Chemical Engineering Research Bulletin 15 (2011) 6-11